(untitled) (Journal of Comparative Social Work, 2010)
Karen Healy uses the term reflection in action to refer to processes of refining knowledge in action so as to promote new ways of responding to the problems we encounter in practice. Thus, social work entails working with different people with different non routine challenges that needs reflective action to be dealt with effectively. The importance of reflection in social work cannot be overtly emphasised. After experiencing an emotional circumstance or situation, in reflecting, and through these experiences we can ably find valuable options for professional development. This process is very much in line with critical incident method. This method is described as both an emotional and cognitive process, proceeding from lower to higher levels of reflection, from analysing the experiences to conceptualizing new knowledge.